2011
DOI: 10.5424/fs/20112003-11481
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure and composition of two Pinus nigra subsp. salzmannii forests over a century of different silvicultural treatments

Abstract: Silvicultural treatments imply the felling of trees, which can modify species composition and structural diversity. Consequently, it is important to assess the influence of silvicultural treatments on forest composition and structure. The principal objective of this study was to analyze changes in the composition and structural diversity of two forests: Los Palancares y Agregados (Cuenca Mountain Range, Central-east of Spain) and Navahondona (Cazorla Mountain Range, Southeast of Spain), managed under two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This silvicultural treatment may explain the lower Nei’s genetic diversity in comparison with the two natural populations of P. nigra from Cuenca’s region (TrCU and ArCU). Tiscar-oliver et al [ 24 ] studied the impact of the management in PaCU and NaCA in the structure and composition of P. nigra populations. The authors concluded that the number of large trees and the diameter classes decrease in both populations over time; however the uneven-aged silvicultural method showed higher values of both variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This silvicultural treatment may explain the lower Nei’s genetic diversity in comparison with the two natural populations of P. nigra from Cuenca’s region (TrCU and ArCU). Tiscar-oliver et al [ 24 ] studied the impact of the management in PaCU and NaCA in the structure and composition of P. nigra populations. The authors concluded that the number of large trees and the diameter classes decrease in both populations over time; however the uneven-aged silvicultural method showed higher values of both variables.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic differences between the Cazorla and Cuenca regions may be due to several factors such as natural barriers, agricultural and forest harvesting, local adaptation and management methods [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both stands are natural; the Beteta stand was managed in 1971, but the El Pozuelo stand has not been managed. Spanish black pine forests in the Cuenca Mountains have traditionally been managed using the shelterwood method, with a shelter-phase of 20-25 years and a rotation period of 100-125 years (Tiscar Oliver et al, 2011). Controlled grazing and hunting-based management are also carried out in the stands.…”
Section: Study Sitementioning
confidence: 99%